Second-order behavior and carrying capacity of 3D asymmetric steel frames with bracing elements - Braz-César, Manuel (2006)
Non-linear P-delta behavior of three-dimensional frames with plan and elevation asymmetries is studied, using a parametric variation of geometry in plan and a stiffness variation along the height. Some behavioral aspects of a calibration frame have been addressed to ascertain the importance of the nodal rigidity (modeled with laminar elements of the type shell with implicit formulation of thick plate or modeled with elastic stiff springs) in the modeling of the geometric non-linearity and stability of such calibration frame. Eurocode 3 criteria for second order analyses is briefly addressed in connection with the 2D frame classification with respect to sway behavior; however for 3D structures the calculated carrying capacity is independent of this classification. So a parametric study of the critical load factor of asymmetric three dimensional frames, unbraced and braced, permits to characterize their carrying capacity with respect to overall structural stability.